Bullying Prevention and Intervention at School Integrating Theory and Research into Best Practices (Springer International Publishing, 2018)
This book examines the continuum of bullying services, including prevention, intervention, and recovery. It reviews current theories, studies, and programs relating to this issue as well as outcome-based solutions to enhance best practices. Chapters discuss prevention and intervention services such as enhancing and promoting teacher skills in identifying abusive behaviors; interventions with bullies, victims, bystanders, and enablers; and curbing digital forms of bullying. International perspectives on program development and delivery offer fresh approaches to conceptualizing a school's particular bullying problems and creating effective policy. In addition, chapters cover program evaluation, guiding principles for evaluators,measurement methods, and documenting and disseminating findings. The book also provides recommendations for program development. Topics featured in this book include: An Adlerian approach to predicting bullying behavior. Bibliotherapy as a strategy for bullying prevention. Coaching teachers in bullying detection and intervention. Cyberbullying prevention and intervention. The "Coping with Bullying" program in Greek secondary schools. Factors that affect reporting victimization in South African schools. Bullying Prevention and Intervention at School is a must-have resource for researchers, clinicians and other practitioners, graduate students, and policymakers across such disciplines as child and school psychology, social work/counseling, pediatrics/school nursing, and educational policy and politics.